GAMBARAN INDIKASI PENCABUTAN GIGI DALAM PERIODE GIGI BERCAMPUR PADA SISWA SMP NEGERI 1 LANGOWAN - Fenanlampir, Inka J.; Mariati, Ni Wayan; Hutagalung, Bernat (Universitas Sam Ratulangi, 2014)
Abstract: Tooth extraction is a process of alveolar dental expenditure, where the tooth is already not possible care anymore. Tooth period is a period of transition when mixed with the date and time of the growth of baby teeth and permanent teeth is considered as vulnerable age and become determinants The purpose of this study was to describe the periods of tooth indication at mixed period on student of SMP Negeri 1 Langowan. Descriptive cross-sectional study with a sample size of 257 students was employed using stratified random sampling technique. The results showed that students who have an indication of tooth extraction on the persistence of mixed tooth period is about 36 students (14%) and students who have dental caries which is an indication of the revocation period is relatively large mixed with 149 students (57.9%). Remained tooth root as indicative of the rest of the students in the revocation mixed period with relatively small teeth itÂ about149 students (25.2%) and the percentage of supernumerary teeth is an indication of the students in the revocation period is relatively small mixed is about 7 students (2.7 %). Keywords: indication of tooth extraction, tooth mixed period.Â Â Abstrak: Pencabutan gigi merupakan suatu proses pengeluaran gigi dari alveolus, dimana pada gigi tersebut sudah tidak dapat dilakukan perawatan lagi. Periode gigi bercampur yaitu masa peralihan saat tanggalnya gigi susu dan saat tumbuhnya gigi tetap dan merupakan usia yang dianggap rawan dan penentu. Tujuan penelitian ini untuk mengetahui gambaran indikasi pencabutan gigi dalam periode gigi bercampur pada siswa SMP Negeri 1 Langowan. Penelitian ini bersifat deskriptif dengan cross sectional study dengan jumlah sampel sebanyak 257 siswa yang diambil dengan teknik Stratified random sampling.Hasil penelitian menunjukkan bahwa siswa yang memiliki indikasi pencabutan gigi persistensi pada periode gigi bercampur sebesar 36 siswa (14%) dan siswa yang memiliki gigi karies yang merupakan indikasi pencabutan pada periode gigi bercampur sebesar yaitu 149 siswa (57,9%). Pada persentase sisa akar yang merupakan indikasi pencabutan pada siswa dalam periode gigi bercampur yaitu sebesar 149 siswa (25,2%) dan persentase supernumerary teeth yang merupakan indikasi pencabutan pada siswa dalam periode gigi bercampur sebesar 7 siswa (2,7%). Kata kunci: indikasi pencabutan gigi, periode gigi bercampur